Mindful sport performance enhancement : mental training for athletes and coaches - Kaufman, Keith A.; Glass, Carol R.; Pineau, Timothy R. (Washington, DC : American Psychological Association, 2018)
This book is a comprehensive resource on the history, theory, and practice of mindfulness in sport. The authors present their empirically-supported, six-session mindfulness program adapted for specific athletic populations.
I. Being a mindful performer. Overcoming the mental training paradox -- The long past but short history of mindfulness in sport -- Going with the flow : mindfulness and peak performance -- II. Mindful sport performance enhancement. MSPE session 1 : building mindfulness fundamentals -- MSPE session 2 : strengthening the muscle of attention -- MSPE session 3 : stretching the body's limits mindfully -- MSPE session 4 : embracing "what is" in stride -- MSPE session 5 : embodying the mindful performer -- MSPE session 6: ending the beginning -- III. Mindful sport performance enhancement : theory, research, practice, and beyond. Pathways from MSPE to peak performance -- Empirical support for MSPE -- Tips for participants : getting the most out of MSPE -- Tips for leaders : enhancing the effectiveness of MSPE -- Performance application beyond sport -- IV. Case study 1 : John the outfielder -- Case study 2 : Angie the basketball coach.
Includes bibliographical references and index.
Keywords: Sports -- Psychological aspects; Athletes -- Psychology; Sports -- Psychological aspects; Athletes -- Psychology